PEMBERDAYAAN MASYARAKAT BERBASIS PARIWISATA - Sochimin Sochimin (Fakultas Ekonomi dan Bisnis Islam (FEBI), Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2019)
Tourism in Indonesia has worldwide because of its diverse tourism potential and extensive natural beauty. However, this does not make the community around the tourist sites enjoy many benefits from the development of aspects of tourism in their area because it requires the public to understand the tourism potential needed in their area, so that the government has the duty and responsibility to empower the community so that the community can use the tourism potential. The concept of community empowerment is based on concepts that represent the community not only as objects, but also as subjects. In the object position, the goal is the community which still needs to be given guidance or direction so that management can continue to develop and achieve goals, while the subject position is the community is the determinant in the development itself, the community is a very important aid in the development planning that has been carried out. Tourism is one of the new industries that is able to increase economic growth quickly in terms of employment opportunities, incomes, living standards and in terms of activating other production sectors in tourist recipient countries. Therefore, the development of locally based tourism does not directly involve the community to actively participate in developing the potential that exists in their area so that they can improve their welfare.